Landslides and engineered slopes. experience, theory and practice : proceedings of the 12th International Symposium on Landslides (Napoli, Italy, 12-19 June 2016) /: proceedings of the 12th International Symposium on Landslides (Napoli, Italy, 12-19 June 2016). (2018) - Unknown
No abstract available